Monetary Transmission through Shadow Banks. (4th October 2019) - Xiao, Kairong
Abstract: I find that shadow bank money creation significantly expands during monetary-tightening cycles. This "shadow banking channel" offsets reductions in commercial bank deposits and dampens the impact of monetary policy. Using a structural model of bank competition, I show that the difference in depositor clienteles quantitatively explains banks' different responses to monetary policy. Facing a more yield-sensitive clientele, shadow banks are more likely to pass through rate hikes to depositors, thereby attracting more deposits when the Federal Reserve raises rates. My results suggest that monetary tightening could unintentionally increase financial fragility by driving deposits into the uninsured shadow banking sector. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.